Hubungan Efikasi Diri dengan Kecurangan Akademik Mahasiswa - Monica Annurianti; Dina Sukma (MASALIQ, 2024)
This study aims to describe self-efficacy and academic dishonesty among students in the X program cohort of 2021-2023, and to identify the relationship between self-efficacy and academic dishonesty in these students. The research is a descriptive correlational quantitative study. The sample consists of 216 students from the X program cohort of 2021-2023, selected using the incidental sampling method. Data collection was conducted through questionnaires on self-efficacy and academic dishonesty among the students. The collected data were analyzed using statistical analysis techniques and tested with the Spearman's rho correlation formula. The results of this study indicate that: (1) The level of self-efficacy in the X program cohort of 2021-2023 is in the very low category, with a percentage of 75.93%. (2) The level of academic dishonesty in the X program cohort of 2021-2023 is in the very high category, with a percentage of 41.20%. (3) Correlation analysis shows a significant and negative relationship between self-efficacy (variable X) and academic dishonesty (variable Y) among students in the X program cohort of 2021-2023, with a correlation coefficient (r) of -.775 and a significance level of 0.000.